Genealogi dan Transformasi Ideologi Partai berbasis Islam di Indonesia Pasca Orde Baru - M Faishal Aminuddin; Romel Masykuri (Islamica: Jurnal Studi Keislaman, 2015)
Study of political Islam did not paid attention to observing the patterns of thought and its transformation in political organization. Even though some studies conducted and brought analysis with case study against specific in their respective political parties. This article departs from the question of how the genealogy of political Islam thought and how it transformed into Islamic-base political parties in democratic Indonesia? The unit of analysis of this study is Islamic-based parties, having a main support base from Islamic religious organizations and had seat in parliament since 1999 election. This study reveals an important finding that Islamic-based parties had been undertakes adaptation and transforming political Islam doctrinaire with more flexible. This is proven through the tracing of consistency between values, platform and the party's work program either in parliament or the public. This study combines historical discursive approach and genealogy as an analytical framework.